A new green pitviper of the Trimeresurus albolabris complex (Reptilia, Serpentes, Viperidae) from central and southern Myanmar - Vogel, Gernot; Nguyen, Tan Van; David, Patrick (Zootaxa, 2023)
In the frame of our investigations on the systematics of the complex of species of Trimeresurus albolabris, we came across specimens from Myanmar variously referred to as Trimeresurus albolabris Gray, 1842 or T. septentrionalis Kramer, 1977 in the literature. We describe a new species of green pitviper of the genus Trimeresurus Lacépède, 1804 from central and southern Myanmar based on molecular analyses drawn from previously published phylogenies and new morphological data. This new species, Trimeresurus uetzi sp. nov., is broadly similar to both Trimeresurus albolabris and T. septentrionalis, but it differs from these latter species by a series of morphological characters such as presence of white pre- and postocular streaks in male, iris copper in male or green gold in female, more ventral plates, and a much shorter hemipenis. We compare this new species with Trimeresurus albolabris as currently defined and other species of this complex. We also emphasize the need for additional integrated studies on Trimeresurus albolabris sensu lato populations distributed in southern Indochina and Sundaland.